The life and writings of Julio C. Tello : America's first indigenous archaeologist - Burger, Richard L. (University of Iowa Press, 2009)
The father of Peruvian archaeology, Julio Tello was the most distinguished Native American scholar ever to focus on archaeology. A Quechua speaker born in a small highland village in 1880, Tello did the impossible: he received a medical degree and convinced the Peruvian government to send him to Harvard and European universities to master archaeology and anthropology. He then returned home to shape modern Peruvian archaeology and the institutions through which it was carried out. This volume thus makes available for the first time a broad sampling of Tello's writings as well as complementary e.